Islam Transformatif: Conceptualizing Liberation Theology for Indonesian Muslim Society - Akmaliah, Wahyudi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This article examines the concept of Islam Transformatif as espoused by Moeslim Abdurrahman, situated within the socio-political context of the Suharto regime. This period witnessed economic growth that overshadowed systemic poverty among Indonesian Muslims. To construct a social justice framework that advocates for the lower classes Abdurrahman reinterprets Marxist perspectives through Islamic lenses, resulting in a transformative Islamic theology known as Islam Transformatif. This study situates this concept within the broader discourse of Islamic liberation theology, emphasizing its response to economic inequality and structural class struggles that have been marginalized in Indonesian social science debates. Abdurrahman’s approach not only broadens the discussion of Islamic liberation theology but also critiques the dearth of political economy perspectives in the study of Indonesian Muslim societies. As a Southeast Asian thinker, Abdurrahman universalizes social science beyond the Eurocentric framework, discussing contemporary issues such as poverty amidst terrorism, redefining hijrah in the context of exploitation, and encouraging Muhammadiyah and Nahdlatul Ulama to adopt Islam Transformatif in combating oligarchical and predatory politics. This concept remains a relevant and important knowledge framework for addressing socio-political challenges in contemporary Indonesia.